Phthalates: The Main Issue in Quality Control in the Beverage Industry - Alessia Iannone; Cristina Di Fiore; Fabiana Carriera; Pasquale Avino; Virgilio Stillittano (Separations, 2024)
Phthalate esters (PAEs) are a group of chemicals used to improve the flexibility and durability of plastics. The chemical properties and the resistance to high temperatures promote their degradation and release into the environment. Food and beverages can be contaminated by PAEs through the migration from packaging material because they are not covalently bound to plastic and also via different kinds of environmental sources or during processing. For instance, alcoholic drinks in plastic containers are a particular risk, since the ethanol contained provides a good solubility for PAEs. According to its role as an endocrine disruptor compound and its adverse effects on the liver, kidney, and reproductive and respiratory systems, the International Agency on Research Cancer (IARC) classified di-(2-ethylhexyl) phthalate (DEHP) as a possible human carcinogen. For this reason, to control human exposure to PAEs, many countries prohibited their use in food as non-food substances. For example, in Europe, the Commission Regulation (EU) 2018/2005 restricts the use of DEHP, dibutyl phthalate (DBP), benzyl butyl phthalate (BBP), and diisobutyl phthalate (DiBP) to a concentration equal to or below 0.1 by weight in plasticizers in articles used by consumers or in indoor areas. There are reports from the US Food and Drug Administration (FDA) that some beverages (and food as well), particularly fruit juices, contain high levels of phthalates. In some cases, the deliberate adulteration of soft drinks with phthalate esters has been reported. This paper would like to show the difficulties of performing PAE analysis in beverage matrices, in particular alcoholic beverages, as well as the main solutions provided for quality control in the industrial branches.